Governing Natural Resources for Africa’s Development - Besada, Hany Gamil (Taylor & Francis., 2016)
Bringing together some of the world’s leading thinkers and policy experts in the area of natural resource governance and management in Africa, this volume addresses the most critical policy issues affecting the continent’s ability to manage and govern its precious resources. The narrative of the book is solutions-driven, as experts weigh on specific issues within the context of Africa’s natural resource governance and offer appropriate policy recommendations on how best to manage the continent’s resources. This is a must-read for government policy makers in industrialized economies and, more importantly, in Africa and emerging economies, as well as for academic researchers working in the field, extractive companies operating on the continent, extractive industry and trade associations, and multilateral and donor aid institutions
Keywords: Development; Governing; Natural resources